Online Buyers and Open Innovation: Security, Experience, and Satisfaction - Luis Enrique Valdez-Juárez (Journal of Open Innovation: Technology, Market and Complexity, 2021)
The topic of consumer behavior in a social context is important due to its influence on the behaviors and attitudes of individuals. New online business models are adopting open innovation practices focused on improving their sales channels through their technological capacity. In this paper, we analyze the purchase intentions in a business context to identify consumer needs through the proper purchase decision process. We must also observe the internal and external factors that influence consumer behavior. More exactly, electronic commerce is facing challenges and opportunities manifested by online consumers, such as design, security, trust, risk, uncertainty, and satisfaction with online purchases. Many external factors (economic, political, social, environmental, and health) influence buyers’ intentions and behaviors. The objectives of this study are to (1) determine the influence of the security level of websites on purchasing behaviors (socially responsible and panic buyers), (2) determine the effect of website security on consumer satisfaction, (3) determine the effect of buyers (socially responsible and panic buyers) on the level of satisfaction, and (4) examine if the buyer experience has a moderating effect between the variables (socially responsible and panic buyers) and the dependent variable (customer satisfaction). We focus on a sample of 663 socially responsible online buyers and panic buyers from the Sonora, Baja California, and Sinaloa regions in Mexico. Data were collected from the months of April to August 2020, and an online questionnaire was used address to each of the residents of these regions aged between 20 and 55 and who were economically active. The data were analyzed using the structural equation model–partial least squares (SEM-PLS) model based on variance. The findings show that website security has significant positive effects on socially responsible buyers, panic buyers, and the level of customer satisfaction. Socially responsible buyers also have positive effects on customer satisfaction. However, the relationship between panic buyers and customer satisfaction is not supported. Related to a moderation analysis, that the buyer experience has a significant effect on the relationship between socially responsible online buyers and the level of satisfaction. Conversely, we find empirical evidence of the buyer experience having no significant effect between panic buyers and customer satisfaction. Our findings contribute to the development of various theories: the theory of behavioral reasoning (BRT), social identity theory (SIT), and the technological adaptation model (TAM). From an academic point of view, the findings are positive and encouraging, contributing to the literature on the e-commerce, behaviors, and attitudes of purchase intentions of individuals. Our work is incorporated into the existing literature on purchase intention and virtual business models, whose characteristics need to continue to be outlined, constituting a popular business model in recent years.